"I'm a hurler … basically just a hurler": a mixed methods study of the athletic identity of elite Irish Gaelic Athletic Association dual career athletes. Issue 3 (4th May 2022) - Geary, Marion; Campbell, Mark; Kitching, Niamh; Houghton, Frank
ABSTRACT: The purpose of this study was to examine the manifestation of the unique cultural backdrop of the Gaelic Athletic Association (GAA) (the historical and political underpinnings of the GAA; the promotion of elite GAA athletes as amateurs despite the increased professionalism in the sports; the significance of the club culture in the GAA) in the athletic identity of elite GAA dual career athletes (DCAs). A mixed methods research (MMR) design was adopted using quantitative and qualitative elements. Elite GAA DCAs ( n  = 9) representing the sports of hurling and Gaelic football simultaneously completed the Athletic Identity Measurement Scale (AIMS) and engaged in semi-structured interviews. Athletic identity data were analysed from the completed AIMS and semi-structured interview data were analysed using a 6-step thematic analysis as per Braun et al. (2016). Eight of the DCAs measured "high" on the AIMS and athletic identities were largely reflective of the elite athlete performance narrative in line with the increased professionalism in the sports. The impact of the club culture in the GAA was evident particularly in the public athletic identity, exclusivity, and negative affectivity dimensions of athletic identity. The niche cultural backdrop of the GAA was manifest in all four dimensions of athletic identity in elite GAA DCAs, with the impact variable on an individual basis. This, along with the prevalence of an elite athlete performance narrative in the expression of their athletic identity needs to be considered regarding dual career (DC) engagement and support.